Changing the Narrative: Settler Colonialism, Food and the Columbia River Treaty - Wagner, John (Anthropologica, 2023)
While the written terms of the Columbia River Treaty appear to justify the often-heard claim that it is all about hydropower and flood control, a full account of its history reveals its critical importance to US agriculture and close relationship to early phases of colonization and development in the Upper Columbia River Basin. In this paper I argue that the Treaty is best understood as the third phase in the last large-scale government-sponsored settler colonialism project in North America, a project that began with the construction of the Grand Coulee Dam in the 1930s. I further argue that the dominant narrative that informs current efforts by Canada and the US to revise the treaty does not fully recognize the settler colonial structure of the original treaty or its critical impact on both Indigenous and settler food systems throughout the basin. I begin with a description of the history of the treaty, in order to demonstrate its continuity with earlier phases of settler colonialism, then focus on its impact on food systems. I conclude with an assessment of the ongoing Canada/US treaty review and renegotiation process that began in 2011 with suggestions for how the process could be brought into better alignment with the United Nations Declaration on the Rights of Indigenous Peoples and the Calls to Action of the Truth and Reconciliation Commission of Canada.